A THEORETICAL VISION OF THE METHODOLOGY OF MATCHING AND CONGRUENCE - Ja’id Muhsin, Hameed (ALBAHITH ALALAMI, 2020)
Perhaps the issue of media and the press, especially one of the most common topics that people deliberate and deal with permanently and continuously. An issue of such significance has pushed researchers to put the following question, “Is it possible to live without media?”, “Can people ignore the newspaper, radio, TV, or the other communication means?”The answer is very simple. It is difficult for civilized society to overtake information, or dispense with circulation, at the individual or collective level. Yet, the question of how to make the media and how it determines its content still requires extensive media experience; and knowledge of the social structure and its relations; and acquaintance with the media theory and its foundations.All this led researchers and theorists in media to follow and study the media topics and dive into them to a large degree. With the enormity of media literary production, there are still many media topics need to be studied and researched with detecting its components.Hence, the significance of this study is founded as a simple initial contribution in a new field of media has not been addressed before.